Pola Peningkatan Suhu Udara Berdasarkan Data Bmkg Dan Era5 Di Provinsi Sulawesi Tengah - Solih Alfiandy; Imron Ade Rangga; Donaldi Sukma Permana (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2022)
Studies on the trend analysis of surface air temperature have never been conducted in Central Sulawesi Province. This study aims to determine changes in the average surface air temperature trend in Central Sulawesi Province period 1981 to 2019. Linear regression analysis is used to identify the trend of temperature changes over a certain period. The results show that the average surface air temperature is significantly increased by 0.015–0.045°C per year (p < 0.05). The results provide the information on climate change analysis that the average surface air temperature has increased in Central Sulawesi Province over 39 years.